2014
DOI: 10.1088/1742-5468/2014/03/p03018
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing traffic-driven epidemic spreading by use of the efficient routing protocol

Abstract: Abstract. Despite extensive work on the interplay between traffic dynamics and epidemic spreading, the control of epidemic spreading by routing strategies has not received adequate attention. In this paper, we study the impact of efficient routing protocol on epidemic spreading. In the case of infinite node-delivery capacity, where the traffic is free of congestion, we find that that there exists optimal values of routing parameter, leading to the maximal epidemic threshold. This means that epidemic spreading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 46 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…For traffic flow dynamics on complex networks, an essential ingredient is the routing strategy. In the model, one can demonstrate that epidemic spreading can be modulated or controlled through a proper choice of the local routing strategy [27] or global routing protocol [28]. For a fixed routing strategy, the network structure can also affect the spreading dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…For traffic flow dynamics on complex networks, an essential ingredient is the routing strategy. In the model, one can demonstrate that epidemic spreading can be modulated or controlled through a proper choice of the local routing strategy [27] or global routing protocol [28]. For a fixed routing strategy, the network structure can also affect the spreading dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the epidemic threshold in the SIS model decreases as flow increases, and emergence of traffic congestion slows down the spread of epidemics. Then, Yang et al [26,27] further studied the relation between traffic dynamics and the SIS epidemic model, and found that the epidemic can be controlled by fine tuning the local or global routing schemes. Furthermore, they obtained that the epidemic threshold can be enhanced by cutting some specific edges in the network [28].…”
Section: Epidemiological Dynamicsmentioning
confidence: 99%
“…In the area of communication networks, [56] modelled epidemic dynamics by considering data packets as the infection agents traveling between random source-destination pairs. Taking [56] as the modelling basis, [57] and [58] have studied the question on how to control epidemic spreading by link removals and via different routing schemes respectively. These works assumed stochastic interactions between node pairs.…”
Section: Background Basics and Related Workmentioning
confidence: 99%